The dilemma of environmental impact assessment in Sarawak, Malaysia - Tang, Daniel Kuok Ho (2021)
In the Malaysian state of Sarawak, Environmental Impact Assessment (EIA) is governed by both the State and the Federal EIA laws. This leads to ambivalence in determining the legislation under which a prescribed activity demanding an EIA falls. Even though a prescribed activity is defined by the EIA legislation, different stages of the prescribed activity eventually become prescribed activities on their own, which demand fulfillment of different EIA legislation. Unclear demarcation of EIA jurisdiction and different requirements on the scope of an EIA particularly for earthworks also stir doubts among environmental consultants. Consultation, involvement and effective communication among the State and Federal environmental authorities are crucial to minimize uncertainty resulted from co-implementation of both the EIA legislation.